Novel solar water filter with long shelf-life - Lim, Hong Ngee; Ariffin, Siti Normaimunah; Huang, Nay Ming (2014)
The utility invention relates to a novel solar water filter with long shelf life. The utility invention provides for water purification by using hydrothermal method 5 with graphene and catalyst. The utility invention has dual functions as absorbent and photocatalyst that degrades organic molecules under the solar light. The ability to photocatalyze enables it to have long shelf-life. Further, the product can be removed for cleaning very easily which ultimately decreases equipment and line downtime.